VR-Electricians: Immersive storytelling for attracting students to the electrical construction industry. (October 2021) - Wen, Jing; Gheisari, Masoud
Highlights: Immersive storytelling can attract students to the electrical construction industry. VR-Electricians uses 360-degree immersive sites with virtual electricians. VR-Electricians was assessed using a pretest-posttest design. VR-Electricians significantly enhanced several aspects of students' attitude. VR-Electricians was rated positively for system usability and social presence. Abstract: Although it is projected to have significant employment growth in the electrical construction industry, there are not enough young people to join the workforce. It is indispensable for the future of work in construction to explore emerging technologies and effectively attract the younger generation to the construction industry. This paper explores the innovative use of 360-degree immersive environments powered by virtual electricians to tell success stories of the electrical construction trades on the field ( VR-Electricians ) and understand how such an immersive storytelling approach can attract young people to join the industry. A pretest-posttest design was used for the VR-Electricians assessment. VR-Electricians was found to significantly enhance several aspects of students' attitude towards the electrical construction industry. VR-Electricians was also rated as a highly usable and easy-to-use system. The outcomes of this study provide construction researchers and practitioners an understanding of how immersive storytelling can be used as a powerful technology-mediated method for attracting students to their field.